Correlation Analyses of Particle Size Distribution, and California Bearing Ratio of Lateritic Soil in Benin City - N., Kayode-Ojo; J.O., Odemerho; T.C., Odimegwu (INTI International University, 2023)
This report presents a correlation analysis conducted to investigate the relationship between particle size distribution and the California Bearing Ratio (CBR) of lateritic soil in Benin City. Field and laboratory investigations were conducted to collect one hundred soil samples, analysis on particle size distribution, and CBR tests were employed. Pearson correlation analysis was performed to quantify the linear relationship between CBR and the percentage of fine particles passing through different sieves. The findings indicated a weak negative correlation between CBR and fine sand content, indicating that an increase in fine sand corresponded to a slight decrease in CBR. A moderate negative correlation was found between CBR and silt/clay content, indicating that as the percentage of these particles increased, CBR values decreased, indicating a decrease in subgrade strength. No linear relationship was observed between CBR and coarse sand content. The study provides valuable insights into the relationship between particle size distribution and CBR of lateritic soil in Benin City, which can be useful for geotechnical engineering and construction projects in the region. The results suggest that the presence of finer particles, particularly silt and clay, can significantly influence the load-bearing capacity of the soil. Further research is recommended to validate and refine the observed correlations and to consider other factors that may affect the soil's engineering behaviour.